Pelatihan Pembuatan Eco-Enzyme: Solusi Ramah Lingkungan untuk Mengurangi Polusi Lingkungan - Sri Wahyuningsih; Nur Ihda Farikhatin Nisa; Ade Trisnawati (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2023)
The primary source of income for the residents of Kenongorejo Village in Madiun Regency is agriculture. The village is situated in a mountainous region. This village produces an increasing amount of agricultural waste due to the abundance of agricultural products. Environmental pollution may result from the amount of agricultural waste that has not been appropriately recycled. Even if part of the agricultural waste has been used as animal feed, the residents of this village still have a concern with the vast amount that has been wasted. It takes environmentally responsible technologies to transform these agricultural wastes into products with a marketable value. The service team's recommendation is to offer training sessions on the production of eco-enzymes, which source their primary raw material from agricultural waste. In order to improve comprehension and abilities in creating eco-enzymes, the strategy employed in this community service activity includes identifying partner requirements, counselling, training, evaluation, and monitoring, as well as post-activity help. The majority of the women of PKK Kenongorejo Village are the main audience for this project. Eco-enzymes, which can be utilised for domestic requirements and sold to the general public as natural cleaning solutions, are the end products of this service activity.